Following the Action of Atypical Antipsychotic Clozapine and Possible Prediction of Treatment Response in Schizophrenia - Mihai-Gabriel Năstase; Antonia Ioana Vasile; Arina Cipriana Pietreanu; Simona Trifu (Life, 2025)
We tried to synthesize the possibilities of predicting the response to clozapine treatment, which can significantly improve the efficacy of the active substance and reduce adverse reactions, and how the active substance acts at the D1 dopaminergic receptors D2, D3, D4, and D5, muscarinic M1, M2, M3, and M5, and the histamine and alpha 1 adrenergic receptor, as well as how it contributes to increased cerebral blood flow, the effect on ribosomal protein S6 function, or the effect on kynurenine 3-monooxygenase function. Clozapine is one of the most effective antipsychotics, and there is potential to improve performance by combining it with different compounds to limit adverse effects or by augmenting it with other antipsychotics (amisulpride, paliperidone), other active substances with different properties (minocycline, N-acetylcysteine, memantine), or alternative therapies (electroconvulsive therapy, repetitive transcranial magnetic stimulation). There are also significant steps in optimizing clozapine efficacy by predicting treatment response, which could be determined by testing the following: plasma levels of clozapine N-oxide and N-desmethylclozapine, serum levels of neurotrophins and glutamate, genetic testing, the polygenic risk score, morphometry, or even the identification and accurate determination of persistent negative symptoms.